Tetrahydroquinoline-amine metal catalyst and preparation method and application thereof
By developing tetrahydroquinoline-amine-based metal catalysts, the problem of insufficient temperature resistance performance of existing catalysts at high temperatures has been solved, and high catalytic activity and efficient synthesis of polyolefin elastomers has been achieved, especially in the synthesis of polyolefin elastomers. The α-olefin insertion rate and polymer quality were significantly improved.
Patent Information
- Application Number
- CN202411535533.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-31
- Publication Date
- 2025-01-07
- Estimated Expiration
- 2044-10-31
AI Technical Summary
When existing catalysts catalyze the synthesis of polyolefin elastomers at high temperatures, there are problems of insufficient temperature resistance and low catalytic activity, which affects the quality and efficiency of the polymer.
A tetrahydroquinoline-amine metal catalyst was developed, which was prepared in the reaction of metal salts and tetrahydroquinoline-imine ligands, using specific solvents and reaction conditions to form high catalytic activity and high temperature resistance. and used in polymerization reactions to increase the molecular weight and α-olefin insertion rate of the polymer.
It has achieved simple synthesis of catalysts, easy raw materials, high product yield and high catalytic activity. It is suitable for high-quality and high-performance polyolefin materials for high-temperature solution polymerization, especially in the synthesis of polyolefin elastomers, which significantly improves α- Olefin insertion rate and polymer mass.
Smart Images

Figure CN119039343B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of polymer compounds, and specifically relates to a tetrahydroquinoline-amine metal catalyst and a preparation method and application thereof. Background Art
[0002] Polyolefin elastomer (POE) is a vinyl random copolymer with a high α-olefin content (usually more than 20wt.%), which is copolymerized with ethylene and 1-octene, 1-hexene or 1-butene. Polyolefin elastomers are a class of high-performance polyolefins with excellent mechanical and elastic properties, and have attracted much attention in the automotive industry and photovoltaic fields. Generally speaking, polyolefin elastomers are synthesized by solution polymerization technology, and solution polymerization is best carried out at high temperatures (usually more than 120°C) to prevent the polymer from precipitating during the polymerization process. Therefore, it is very necessary to develop homogeneous metal catalysts with better catalytic performance at high temperatures. To this end, researchers around the world designed and synthesized metallocenes and constrained geometry catalysts (CGC) and began to successfully use them in the commercial production of POE in the early 1990s. In addition, many non-metallocene transition metal catalysts have also gradually developed. Dow scientists successfully improved the high temperature resistance of the catalyst by introducing a quinoline structure into the catalyst skeleton (Organometallics 2012, 31, 6244-6251), and obtained a series of polyolefin catalysts with different catalytic properties by changing the substituents on the catalyst structure. Furthermore, scientists also studied the effect of the flexible skeleton on the catalytic performance (Organometallics 2021, 40, 242-252). Summary of the invention
[0003] The purpose of the present invention is to provide a tetrahydroquinoline-amine metal catalyst, which has the advantages of simple synthesis, easy availability of raw materials, high activity, excellent high temperature resistance and high product yield; the present invention also provides a preparation method and application of the tetrahydroquinoline-amine metal catalyst.
[0004] The tetrahydroquinoline-amine metal catalyst of the present invention has the following structural formula:
[0005]
[0006] Wherein, M is one of titanium, zirconium or hafnium, X is one of methyl, benzyl or -Cl, R 1 is one of methyl, ethyl, isopropyl or -H, R 2 is one of methyl, ethyl, isopropyl or -H, R 3 is one of methyl, methoxy, tert-butyl or -H, R 4 It is one of a C1-C6 straight-chain alkyl, a phenyl group or a benzyl group.
[0007] The method for preparing the tetrahydroquinoline-amine metal catalyst of the present invention comprises the following steps:
[0008] (1) Under a nitrogen atmosphere, dissolve the metal salt in an anhydrous solvent and add methylmagnesium bromide solution to react;
[0009] (2) Adding a tetrahydroquinoline-imine ligand to the reaction in the dark, continuing the reaction after the reaction is completed, removing the solvent under reduced pressure, adding a good solvent for extraction, filtering, and obtaining a tetrahydroquinoline-amine metal catalyst.
[0010] In step (1), the metal salt is one of TiCl4, ZrCl4 or HfCl4.
[0011] The solvent in step (1) is one of toluene, n-hexane, xylene or benzene.
[0012] In step (1), the ratio of metal salt, anhydrous solvent and methyl magnesium bromide solution is 0.2-0.36:10-15:1.5-1.8, wherein the metal salt is measured in g, the anhydrous solvent is measured in ml, and the methyl magnesium bromide solution is measured in ml.
[0013] The concentration of the methylmagnesium bromide solution in step (1) is 2.8-3.2M.
[0014] In step (1), the reaction temperature is -45 to -35°C and the reaction time is 1 to 3 hours.
[0015] The preparation method of the tetrahydroquinoline-imine ligand in step (2) is to add 2-formyl-tetrahydroquinoline, an aniline compound and p-toluenesulfonic acid to a solvent for reaction, concentrate under reduced pressure, filter, and dry to obtain the tetrahydroquinoline-imine ligand; wherein the aniline compound is 2,6-dimethylaniline or 2,6-diisopropylaniline, the solvent is ethanol, and the mass ratio of 2-formyl-tetrahydroquinoline, the aniline compound and p-toluenesulfonic acid is 1.61:1.2-1.8:0.02-0.03; the ratio of the aniline compound to the solvent is 1.2-1.8:100, wherein the aniline compound is measured in g and the solvent is measured in ml; and the reaction temperature is 25-27°C.
[0016] The mass ratio of the tetrahydroquinoline-imine ligand in step (2) to the metal salt in step (1) is 0.26-0.32:0.2-0.36.
[0017] The temperature of the light-proof reaction in step (2) is -45 to -35°C, and the light-proof reaction time is 1 to 3 hours.
[0018] The temperature for continuing the reaction in step (2) is room temperature, and the time for continuing the reaction is 4-6 hours.
[0019] In step (2), the good solvent is one of n-hexane, toluene, pentane, heptane or cyclohexane.
[0020] The application of the tetrahydroquinoline-amine metal catalyst of the present invention is that olefin monomer, tetrahydroquinoline-amine metal catalyst and co-catalyst are polymerized in a solvent to obtain a polymer.
[0021] The olefin monomer is one or more of ethylene, propylene, 1-butene, 1-hexene or 1-octene; the cocatalyst is one or more of tri(pentafluorophenyl)boron, triphenylcarbonium tetra(pentafluorophenyl)borate, aluminoxane, alkylaluminum or alkylaluminum chloride; the aluminoxane is one of methylaluminoxane, ethylaluminoxane or isobutylaluminoxane; the alkylaluminum is one of trimethylaluminum, triethylaluminum, triisobutylaluminum or tri-n-hexylaluminum; the alkylaluminum chloride is one of diethylaluminum monochloride, diethylaluminum sesquichloride or ethylaluminum dichloride; the solvent is one or more of n-hexane, n-heptane, n-pentane or toluene.
[0022] The polymerization reaction temperature is 80-180°C, and the polymerization reaction pressure is 1-5MPa.
[0023] The structural formula of the tetrahydroquinoline-amine metal catalyst of the present invention is preferably one of the following structural formulas:
[0024]
[0025] In the present invention, 2-formaldehyde-tetrahydroquinoline and aniline compounds are subjected to p-toluenesulfonic acid (TsOH)-catalyzed amine-aldehyde condensation to synthesize tetrahydroquinoline-imine ligands, and the tetrahydroquinoline-imine ligands react with MMe4 (M = Ti, Zr or Hf) synthesized in situ in a one-pot reaction to obtain a tetrahydroquinoline-amine metal catalyst, which has high yield and great economic benefits. The obtained tetrahydroquinoline-amine metal catalyst is used in the synthesis of polyolefin elastomers, and it is found that by changing the substituents on the catalyst structure, the molecular weight and α-olefin insertion rate of the obtained polymer can be effectively improved.
[0026] The beneficial effects of the present invention are as follows:
[0027] The tetrahydroquinoline-amine metal catalyst prepared by the present invention has the advantages of simple synthesis, easy availability of raw materials, high product yield, high catalytic activity (the highest activity can reach 5.65×10 8 g(POE)·mol -1 (M) ·h -1 ), good copolymerization performance (α-olefin insertion rate can reach up to 48.3mol%), and is particularly suitable for high-temperature solution polymerization to prepare high-quality, high-performance polyolefin materials. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] Figure 1This is the carbon NMR spectrum of the polymer obtained in Example 14.
[0029] Figure 2 This is the carbon NMR spectrum of the polymer obtained in Example 15.
[0030] Figure 3 This is the NMR carbon spectrum of the polymer obtained in Example 16.
[0031] Figure 4 is a gel permeation chromatogram of the polymer prepared in Example 22.
[0032] Figure 5 is a gel permeation chromatogram of the polymer prepared in Example 23.
[0033] Figure 6 is a gel permeation chromatogram of the polymer obtained in Example 24. DETAILED DESCRIPTION
[0034] The present invention is further described below with reference to the embodiments.
[0035] Example 1
[0036] Preparation of 2-(2,6-Me2-C6H3-N=CH)-tetrahydroquinoline:
[0037] Under a nitrogen atmosphere, 1.61 g of 2-formyl-tetrahydroquinoline, 1.21 g of 2,6-dimethylaniline and 20 mg of p-toluenesulfonic acid were added to 100 mL of ethanol and stirred at 25 °C overnight to obtain a reaction solution. The reaction solution was concentrated under reduced pressure and then filtered. After drying, a yellow powdery solid ligand 2-(2,6-Me2-C6H3-N=CH)-tetrahydroquinoline was obtained with a yield of 90%. 1 H NMR (CDCl3): δ8.40 (s, 1 H), 7.77 (d, J = 8.5 Hz, 1 H), 7.73 (d, J = 8.5 Hz, 1 H), 7.74 (d, J = 8.0 Hz, 1 H), 7.62 (t, J = 6.9 Hz, 1 H), 7.22 (d, J = 8.0 Hz, 1 H), 2.85(s, 6 H), 2.21-2.17 (m, 2 H), 2.03-1.95 (m, 2 H), 1.63-1.58 (m, 2 H), 1.50-1.42 (m, 2 H) ppm. 13C NMR (CDCl3): δ160.00, 157.55, 151.77, 150.90, 136.42,130.81, 128.02, 127.06, 125.66, 118.76, 32.12, 30.10, 24.47, 23.96, 19.22ppm. Anal. Calcd for C 18 H 20 N2: C, 81.78; H, 7.63; N, 10.60. Found: C, 81.85; H, 7.82; N, 10.33.
[0038] The reaction equation is as follows:
[0039]
[0040] Example 2
[0041] 2-(2,6- i Preparation of Pr2-C6H3-N=CH)-tetrahydroquinoline:
[0042] Under nitrogen atmosphere, 1.61 g of 2-formyl-tetrahydroquinoline, 1.77 g of 2,6-diisopropylaniline and 30 mg of p-toluenesulfonic acid were added to 100 mL of ethanol and stirred at 27 ° C overnight to obtain a reaction solution. The reaction solution was concentrated under reduced pressure and filtered. After drying, a yellow powdery solid ligand 2-(2,6- i Pr2-C6H3-N=CH)-tetrahydroquinoline, yield 92%. 1 H NMR (CDCl3): δ8.42 (s, 1 H), 7.78 (d, J = 8.5 Hz, 1 H), 7.70 (d, J = 8.5 Hz, 1 H), 7.66 (d, J = 8.0 Hz, 1 H), 7.50 (t, J = 6.9 Hz, 1 H), 7.18 (d, J = 8.0 Hz, 1 H), 3.25(sept, J = 6.7 Hz,2 H), 2.23-2.19 (m, 2 H), 2.05-1.99 (m, 2 H), 1.60-1.55 (m,2 H), 1.50-1.44 (m, 2 H),1.18 (d, J = 6.7 Hz, 12 H)ppm. 13C NMR (CDCl3): δ161.08, 154.98, 152.76, 144.38, 136.44, 134.72, 130.80, 125.75, 123.83,118.76, 32.88, 30.66, 30.02, 24.48, 23.77, 22.82 ppm. Anal. Calcd for C 22 H 28 N2:C, 82.45; H, 8.81; N, 8.74. Found: C, 82.44; H, 8.77; N, 8.67.
[0043] The reaction equation is as follows:
[0044]
[0045] Example 3
[0046] Preparation of Catalyst C1:
[0047] Under nitrogen atmosphere, weigh 0.256 g of hafnium tetrachloride, add 10 mL of dry toluene, slowly add 1.6 mL of methylmagnesium bromide solution (3 M) at -40 °C (acetonitrile-liquid nitrogen bath), and stir to react for 2 hours; then add 0.26 g of ligand 2-(2,6-Me2-C6H3-N=CH)-tetrahydroquinoline, stir to react for 2 hours at -40 °C in the dark, and continue to react for 5 hours after returning to room temperature; after the reaction, remove the solvent under reduced pressure, extract with toluene, and filter to obtain the product with a yield of 85%. 1 H NMR (400 MHz, C6D6): δ 7.56 (d, J = 8.5 Hz, 1 H), 7.22 (d, J = 8.5 Hz, 1 H), 7.02 (d, J = 8.0Hz, 1H), 6.88 (t, J = 6.9 Hz, 1 H), 6.73 (d, J = 8.0 Hz, 1 H), 4.01 (quatra, J = 7.0 Hz, 1 H), 2.65 (s, 3 H), 2.23 (s, 3 H), 2.20-2.15 (m, 2 H), 2.10-1.99 (m, 2 H), 1.80 (d, J= 7.0 Hz, 3 H), 1.60-1.52 (m, 2 H), 1.50-1.44 (m, 2 H), 0.90 (s, 9 H) ppm. 13 C NMR (400 MHz, C6D6): δ161.60, 160.09, 144.90, 137.10,129.07, 128.35, 128.05, 127.10, 126.16, 121.66, 119.62, 55.23, 48.25, 31.40,28.35, 23.13, 22.75, 22.10, 18.95, 18.02 ppm. Anal. Calcd for C 22 H 32 HfN2: C, 52.53; H, 6.41; N, 5.57. Found: C, 52.43; H, 6.32; N, 5.38.
[0048] The reaction equation is as follows:
[0049]
[0050] Example 4
[0051] Preparation of Catalyst C2:
[0052] Under nitrogen atmosphere, weigh 0.352 g of hafnium tetrachloride, add 15 mL of dry n-hexane, slowly add 1.6 mL of methylmagnesium bromide solution (3 M) at -40 °C (acetonitrile-liquid nitrogen bath), and stir for 2 hours; then add the ligand 2-(2,6- i The mixture was stirred at -40 °C in the dark for 2 hours, and then the reaction was continued for 5 hours after returning to room temperature. After the reaction was completed, the solvent was removed under reduced pressure, and the product was extracted with n-hexane and filtered to obtain the product with a yield of 88%. 1 H NMR (400MHz, C6D6): δ 7.70 (d, J = 8.5 Hz, 1 H), 7.34 (d, J = 8.5 Hz, 1 H), 7.09 (d, J = 8.0 Hz, 1 H), 6.90 (t, J = 6.9 Hz, 1 H), 6.88 (d, J = 8.0 Hz, 1 H), 4.12(quatra, J= 7.0 Hz, 1 H), 3.95 (sept, J = 6.7 Hz, 1 H), 3.21 (sept, J = 6.7Hz, 1 H),2.23-2.19 (m, 2 H), 2.05-1.99 (m, 2 H), 1.82 (d, J = 7.0 Hz, 3 H),1.60-1.55 (m, 2 H), 1.50-1.44 (m, 2 H),1.19 (d, J = 6.7 Hz, 6 H),1.10 (d, J =6.7 Hz, 6 H), 0.96 (s, 9 H) ppm. 13 C NMR (400 MHz, C6D6): δ163.24, 161.22,143.45, 138.15, 129.43, 128.56, 128.15, 127.23, 126.10, 121.26, 119.37,55.77, 48.89, 33.40, 32.98, 31.22, 30.22, 28.35, 23.13, 22.75, 18.95,18.02ppm. Anal. Calcd for C 26 H 40 HfN2: C, 55.85; H, 7.21; N, 5.01. Found: C, 55.83; H, 7.09; N, 5.12.
[0053] The reaction equation is as follows:
[0054]
[0055] Example 5
[0056] Preparation of catalyst C3:
[0057] Under nitrogen atmosphere, weigh 0.256 g zirconium tetrachloride, add 12 mL dry xylene, slowly add 1.5 mL methylmagnesium bromide solution (3.2 M) at -45 °C (acetonitrile-liquid nitrogen bath), stir and react for 3 hours, then add ligand 2-(2,6- i The mixture was stirred at -45°C in the dark for 3 hours, and then the reaction was continued for 4 hours after returning to room temperature. After the reaction, the solvent was removed under reduced pressure, and pentane was added for extraction. The product was filtered to obtain a product with a yield of 84%. 1H NMR (400MHz, C6D6): δ7.62 (d, J = 8.5 Hz, 1 H), 7.30 (d, J = 8.5 Hz, 1 H), 7.15 (d, J =8.0 Hz, 1 H), 6.92 (t, J = 6.9 Hz, 1 H), 6.79 (d, J = 8.0 Hz, 1 H), 4.02(quatra, J = 7.0 Hz, 1 H), 3.91 (sept, J = 6.7 Hz, 1 H), 3.10 (sept, J = 6.7Hz, 1 H),2.28-2.22 (m, 2 H), 2.15-2.07 (m, 2 H), 1.83 (d, J = 7.0 Hz, 3 H),1.63-1.59 (m, 2 H), 1.50-1.46 (m, 2 H),1.18 (d, J = 6.7 Hz, 6 H),1.12 (d, J =6.7 Hz, 6 H), 0.78 (s, 9 H) ppm. 13 C NMR (400 MHz, C6D6): δ165.10, 162.28,143.41, 138.98, 129.93, 128.99, 128.25, 127.88, 126.15, 121.78, 119.30,50.12, 48.43, 32.99, 32.96, 31.23, 30.45, 28.51, 23.23, 22.09, 18.96, 18.23ppm. Anal. Calcd for C 26 H 40 ZrN2: C, 66.18; H, 8.55; N, 5.94. Found: C, 66.02; H, 8.39; N, 5.88.
[0058] The reaction equation is as follows:
[0059]
[0060] Example 6
[0061] Preparation of catalyst C4:
[0062] Under nitrogen atmosphere, weigh 0.209 g of titanium tetrachloride, add 10 mL of dry toluene, slowly add 1.8 mL of methylmagnesium bromide solution (2.8 M) at -35 °C (acetonitrile-liquid nitrogen bath), stir and react for 1 hour, then add the ligand 2-(2,6- i The mixture was stirred at -35°C in the dark for 1 hour, and then the reaction was continued for 6 hours after returning to room temperature. After the reaction, the solvent was removed under reduced pressure, and toluene was added for extraction. The product was filtered to obtain a product with a yield of 80%. 1 H NMR (400MHz, C6D6) δ7.61 (d, J = 8.5 Hz, 1 H), 7.22 (d, J = 8.5 Hz, 1 H), 7.01 (d, J =8.0 Hz, 1 H), 6.80 (t, J = 6.9 Hz, 1 H), 6.71 (d, J = 8.0 Hz, 1 H), 4.23(quatra, J = 7.0 Hz, 1 H), 3.93 (sept, J = 6.7 Hz, 1 H), 3.18 (sept, J = 6.7Hz, 1 H), 2.28-2.20 (m, 2 H), 2.05-2.00 (m, 2 H), 1.88 (d, J = 7.0 Hz, 3 H),1.62-1.55 (m, 2 H), 1.46-1.40 (m, 2 H),1.20 (d, J = 6.7 Hz, 6 H),1.13 (d, J =6.7 Hz, 6 H), 0.65 (s, 9 H) ppm. 13 C NMR (400 MHz, C6D6): δ160.33, 161.25,144.32, 137.66, 129.33, 128.76, 128.32, 127.55, 126.56, 121.12, 119.34,42.55, 40.82, 33.42, 32.92, 31.24, 30.26, 28.37, 23.43, 22.77, 18.97, 18.32ppm.Anal. Calcd for C 26H 40 TiN2: C, 72.88; H, 9.41; N, 6.54. Found: C, 72.72; H, 9.31; N, 6.61.
[0063] The reaction equation is as follows:
[0064]
[0065] Example 7
[0066] Under nitrogen atmosphere, weigh 2µmol of catalyst C1, 2.2µmol of triphenylcarbonium tetrakis(pentafluorophenyl)borate and 100µmol of methylaluminoxane and add them to a 350mL glass reactor equipped with a magnet for polymerization reaction; when the polymerization temperature reaches 80°C, add 50mL of toluene, and continuously introduce ethylene gas during the polymerization process to ensure that the reaction pressure is 5MPa. After reacting for 2 minutes, add 30mL of ethanol to the reactor under nitrogen atmosphere; after cooling, pour the reaction solution into a large amount of ethanol for sedimentation, and obtain the polymer by filtration and drying. Polymerization activity: 52000kg·mol -1 (Hf) h -1 , polymer Mw = 273 kg·mol -1 , Mw / Mn= 2.0.
[0067] Example 8
[0068] Catalyst C1 was replaced by catalyst C2, and the other steps were the same as in Example 7. Polymerization activity: 95500 kg·mol -1 (Hf) h -1 , polymer Mw = 430 kg·mol -1 , Mw / Mn= 2.0.
[0069] Example 9
[0070] Catalyst C1 was replaced by catalyst C3, and the other steps were the same as in Example 7. Polymerization activity: 76500 kg·mol -1 (Zr)·h -1 , polymer Mw = 320 kg·mol -1 , Mw / Mn=2.1.
[0071] Example 10
[0072] Catalyst C1 was replaced by catalyst C4, and the other steps were the same as in Example 7. Polymerization activity: 20500 kg·mol -1 (Ti) h -1 , polymer Mw = 110 kg·mol -1 , Mw / Mn=2.0.
[0073] Embodiment 11
[0074] The polymerization temperature was 120°C, and the other steps were the same as in Example 7. Polymerization activity: 78800 kg·mol -1 (Hf) h -1 , polymer Mw = 261 kg·mol -1 , Mw / Mn=2.2.
[0075] Example 12
[0076] A 100mL steel reactor equipped with a magnet was used for polymerization. In a nitrogen atmosphere, 50mL of toluene was injected with a syringe, the contents of the reactor were heated to 160°C, and the reactor was saturated with 1MPa of ethylene. 2µmol of catalyst C1, 100μmol of methylaluminoxane, and 2.2µmol of triphenylcarbonium tetrakis(pentafluorophenyl)borate were added to the glove box, dissolved in toluene, and transferred to the catalyst storage tube through a syringe. Nitrogen (over 1MPa) was pressed into the reactor. During the polymerization process, ethylene gas was continuously introduced to ensure that the polymerization temperature was 160°C and the polymerization pressure was 1MPa. After reaching the set reaction time of 2min, 2mL of ethanol was pressed into the reactor under nitrogen (over 1MPa), the reactor was cooled and vented, and the contents of the reactor were poured into a large amount of ethanol. The polymer precipitated and filtered to obtain the polymer, which was washed with a small amount of ethanol and finally vacuum dried overnight and weighed. Polymerization activity: 165000kg·mol -1 (Hf) h -1 , polymer Mw = 338 kg·mol -1 , Mw / Mn=2.2.
[0077] Embodiment 13
[0078] The polymerization temperature was 180°C, and the other steps were the same as in Example 12. Polymerization activity: 145300 kg·mol -1 (Hf) h -1 , polymer Mw = 335 kg·mol -1 , Mw / Mn =2.0.
[0079] Embodiment 14
[0080] Under nitrogen atmosphere, weigh 2µmol of catalyst C2, 2.2µmol of triphenylcarbonium tetrakis(pentafluorophenyl)borate and 100µmol of methylaluminoxane and add them to a 350mL glass reactor equipped with a magnet for polymerization reaction; when the polymerization temperature reaches 120°C, add 26.6mL of toluene and 23.4mL of 1-octene, and continuously introduce ethylene gas during the polymerization process to ensure that the reaction pressure is 5MPa. After 2 minutes of reaction, add 30mL of ethanol to the reactor under nitrogen atmosphere; after cooling, pour the reaction solution into a large amount of ethanol for sedimentation, and obtain the polymer by filtration and drying. Polymerization activity: 105050kg·mol -1 (Hf) h -1 , polymer Mw = 560 kg·mol -1 , Mw / Mn=2.1, the content of 1-octene in the polymer is 48.3mol%. The NMR carbon spectrum of the polymer is shown in Figure 1 .
[0081] Embodiment 15
[0082] 26.6 mL toluene and 23.4 mL 1-octene were replaced by 34.4 mL toluene and 15.6 mL 1-octene, and the other steps were the same as in Example 14. Polymerization activity: 101000 kg·mol -1 (Hf) h -1 , polymer Mw = 520 kg·mol -1 , Mw / Mn=2.0, the content of 1-octene in the polymer is 30.1mol%. The NMR carbon spectrum of the polymer is shown in Figure 2 .
[0083] Example 16
[0084] 26.6 mL toluene and 23.4 mL 1-octene were replaced by 42.2 mL toluene and 7.8 mL 1-octene. The other steps were the same as in Example 14. Polymerization activity: 99700 kg·mol -1 (Hf) h -1 , polymer Mw = 480 kg·mol -1 , Mw / Mn=2.2, the content of 1-octene in the polymer is 16.6mol%. The NMR carbon spectrum of the polymer is shown in Figure 3 .
[0085] Embodiment 17
[0086] Catalyst C2 was replaced by catalyst C1, and the other steps were the same as in Example 14. Polymerization activity: 85000 kg·mol -1 (Hf) h -1 , polymer Mw = 550 kg·mol -1, Mw / Mn=2.1, the content of 1-octene in the polymer is 32.6mol%.
[0087] Embodiment 18
[0088] Catalyst C2 was replaced by catalyst C3, and the other steps were the same as in Example 14. Polymerization activity: 62800 kg·mol -1 (Zr)·h -1 , polymer Mw = 484 kg·mol -1 , Mw / Mn=2.4, the content of 1-octene in the polymer is 31.4 mol%.
[0089] Embodiment 19
[0090] Catalyst C2 was replaced by catalyst C4, and the other steps were the same as in Example 14. Polymerization activity: 16250 kg·mol -1 (Ti) h -1 , polymer Mw = 459 kg·mol -1 , Mw / Mn=2.3, the content of 1-octene in the polymer is 15.5mol%.
[0091] Embodiment 20
[0092] A 100 mL steel reactor equipped with a magnet was used for the polymerization reaction. Under a nitrogen atmosphere, a mixture of 26.6 mL toluene and 23.4 mL 1-octene (a total of 50 mL) was injected with a syringe, the contents of the reactor were heated to 120 ° C, and the reactor was saturated with 1 MPa ethylene. 2 µmol of catalyst C2, 100 µmol of methylaluminoxane, and 2.2 µmol of triphenylcarbonium tetrakis (pentafluorophenyl) borate were added to the glove box, dissolved in toluene, and transferred to the catalyst storage tube through a syringe, and then pressurized into the reactor with nitrogen (over 1 MPa). During the polymerization process, ethylene gas was continuously introduced to ensure that the polymerization temperature was 120 ° C and the polymerization pressure was 1 MPa. After reaching the set reaction time of 2 min, 2 mL of ethanol was pressed into the reactor under nitrogen (over 1 MPa), the reactor was cooled and vented, and the contents of the reactor were poured into a large amount of ethanol. The polymer precipitated and filtered to obtain the polymer, which was washed with a small amount of ethanol and finally vacuum dried overnight and weighed. Polymerization activity: 187000 kg·mol -1 (Hf) h -1 , polymer Mw = 630 kg·mol -1 , Mw / Mn=2.1, the content of 1-octene in the polymer is 29.8mol%.
[0093] Embodiment 21
[0094] The polymerization reaction pressure was 2 MPa, and the other steps were the same as in Example 20. Polymerization activity: 263000 kg·mol -1 (Hf) h -1 , polymer Mw = 690 kg·mol -1 , Mw / Mn=2.1, the content of 1-octene in the polymer is 19.0mol%.
[0095] Embodiment 22
[0096] The polymerization reaction pressure was 3 MPa, and the other steps were the same as in Example 20. Polymerization activity: 565000 kg·mol -1 (Hf) h -1 , polymer Mw = 1300 kg·mol -1 , Mw / Mn=2.0, the content of 1-octene in the polymer is 11.5mol%. The gel permeation chromatogram of the polymer is shown in Figure 4 .
[0097] Embodiment 23
[0098] The polymerization temperature was 140°C, and the other steps were the same as in Example 20. Polymerization activity: 189500 kg·mol -1 (Hf) h -1 , polymer Mw = 900 kg·mol -1 , Mw / Mn=2.2, the content of 1-octene in the polymer is 22.0mol%. The gel permeation chromatogram of the polymer is shown in Figure 5 .
[0099] Embodiment 24
[0100] The polymerization temperature was 160°C, and the other steps were the same as in Example 20. Polymerization activity: 145500 kg·mol -1 (Hf) h -1 , polymer Mw = 750 kg·mol -1 , Mw / Mn=2.3, the content of 1-octene in the polymer is 21.3mol%. The gel permeation chromatogram of the polymer is shown in Figure 6 .
Claims
1. A tetrahydroquinoline-amine metal catalyst, characterized in that The structural formula is as follows: Wherein, M is one of titanium, zirconium or hafnium, X is one of methyl, benzyl or -Cl, R 1 is one of methyl, ethyl, isopropyl or -H, R 2 is one of methyl, ethyl, isopropyl or -H, R 3 is one of methyl, methoxy, tert-butyl or -H, R 4 It is one of a C1-C6 straight-chain alkyl, a phenyl group or a benzyl group.
2. A method for preparing the tetrahydroquinoline-amine metal catalyst according to claim 1, characterized in that The steps include: (1) Under a nitrogen atmosphere, dissolve the metal salt in an anhydrous solvent and add methylmagnesium bromide solution to react; (2) adding a tetrahydroquinoline-imine ligand to react in the dark, continuing the reaction after the reaction is completed, removing the solvent under reduced pressure, adding a good solvent for extraction, filtering, and obtaining a tetrahydroquinoline-amine metal catalyst; The preparation method of the tetrahydroquinoline-imine ligand in step (2) is to add 2-formyl-tetrahydroquinoline, an aniline compound and p-toluenesulfonic acid to a solvent for reaction, concentrate under reduced pressure, filter and dry to obtain the tetrahydroquinoline-imine ligand; the aniline compound is 2,6-dimethylaniline or 2,6-diisopropylaniline, and the solvent is ethanol.
3. The method for preparing the tetrahydroquinoline-amine metal catalyst according to claim 2, characterized in that In step (1), the metal salt is one of TiCl4, ZrCl4 or HfCl4, and the solvent is one of toluene, n-hexane, xylene or benzene; the ratio of the metal salt, the anhydrous solvent and the methylmagnesium bromide solution is 0.2-0.36:10-15:1.5-1.8, wherein the metal salt is measured in g, the anhydrous solvent is measured in ml, and the methylmagnesium bromide solution is measured in ml; and the concentration of the methylmagnesium bromide solution is 2.8-3.2M.
4. The method for preparing the tetrahydroquinoline-amine metal catalyst according to claim 2, characterized in that In step (1), the reaction temperature is -45 to -35°C and the reaction time is 1 to 3 hours.
5. The method for preparing the tetrahydroquinoline-amine metal catalyst according to claim 2, characterized in that The mass ratio of the tetrahydroquinoline-imine ligand in step (2) to the metal salt in step (1) is 0.26-0.32:0.2-0.36; the temperature of the light-proof reaction is -45--35°C, and the light-proof reaction time is 1-3 hours; the temperature of the continued reaction is room temperature, and the continued reaction time is 4-6 hours; the good solvent is one of n-hexane, toluene, pentane, heptane or cyclohexane.
6. Use of the tetrahydroquinoline-amine metal catalyst according to claim 1, characterized in that In a solvent, olefin monomers, tetrahydroquinoline-amine metal catalysts and co-catalysts undergo polymerization reaction to obtain polymers.
7. Use of the tetrahydroquinoline-amine metal catalyst according to claim 6, characterized in that The olefin monomer is one or more of ethylene, propylene, 1-butene, 1-hexene or 1-octene; the cocatalyst is one or more of tri(pentafluorophenyl)boron, triphenylcarbonium tetra(pentafluorophenyl)borate, aluminoxane, alkylaluminum or alkylaluminum chloride; the aluminoxane is one of methylaluminoxane, ethylaluminoxane or isobutylaluminoxane; the alkylaluminum is one of trimethylaluminum, triethylaluminum, triisobutylaluminum or tri-n-hexylaluminum; the alkylaluminum chloride is one of diethylaluminum monochloride, diethylaluminum sesquichloride or ethylaluminum dichloride; the solvent is one or more of n-hexane, n-heptane, n-pentane or toluene.
8. The use of the tetrahydroquinoline-amine metal catalyst according to claim 6, characterized in that The polymerization reaction temperature is 80-180°C, and the polymerization reaction pressure is 1-5MPa.
Citation Information
Patent Citations
Preparation method and application of NN-bidentate coordination metal catalyst based on quinoline skeleton
CN118047806A